1993
DOI: 10.1152/jn.1993.70.1.200
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and pain sensations evoked by microstimulation in the area of human ventrocaudal nucleus

Abstract: 1. We have studied the sensations evoked by threshold microstimulation (TMS) in the area of the human principal sensory nucleus of the thalamus [ventralis caudalis (Vc)] in patients (n = 11) undergoing stereotactic surgery for the treatment of movement disorders and pain. Preoperatively, patients were trained to describe somatic sensory stimuli using a standard list of descriptors. This same list was used to describe sensations evoked intraoperatively by thalamic microstimulation. Stimulation sites (n = 216) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
182
2
7

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(206 citation statements)
references
References 0 publications
15
182
2
7
Order By: Relevance
“…Patient 8 (Vc only) showed cold allodynia in response to the brass bar, which is nonpainful in control subjects (Lenz et al, 1993a). Among three patients tested with quantitative testing, one patient had cold allodynia (patient 18), and one had hypoalgesia (patient 13).…”
Section: Formal Sensory Testingmentioning
confidence: 93%
See 1 more Smart Citation
“…Patient 8 (Vc only) showed cold allodynia in response to the brass bar, which is nonpainful in control subjects (Lenz et al, 1993a). Among three patients tested with quantitative testing, one patient had cold allodynia (patient 18), and one had hypoalgesia (patient 13).…”
Section: Formal Sensory Testingmentioning
confidence: 93%
“…A complete neurologic history and physical examination was performed in each case independently by a neurosurgeon and neurologist, including a detailed clinical assessment of somatic sensory function (Lenz et al, 1993a). We next examined the thresholds for innocuous warm, innocuous cool, heat pain, cold pain, and innocuous tactile sensations, as well as the presence of brushing allodynia.…”
Section: Psychophysical Testsmentioning
confidence: 99%
“…Bushnell et al (1993) Recently it was reported that microstimulation in the human lateral thalamus may evoke "cool" and "warm" perceptions (Lenz et al, 1993a). Lenz et al (1993b) have now been able to record from three cooling responsive cells in the lateral thalamus ofthe awake human.…”
Section: Comparison With Other Thalamic Physiologic Studiesmentioning
confidence: 99%
“…More recently, recordings and microstimulation were performed in the lateral thalamus of chronic pain or motor disorder patients (Lenz et al, , 1988(Lenz et al, , 1993aTasker et al, 1987;Dostrovsky et al, 199 1). These studies indicate the existence of a lateral thalamic region, just ventral and posterior to the main somatosensory nucleus, the stimulation of which results in localized contralateral thermal or @ain reports in unanesthetized subjects, and single-unit recordings show a small number of cells with activity correlated with noxious stimulation.…”
Section: Cortical Targetsmentioning
confidence: 99%
“…Similar to CPSP, neuropathic pain after spinal cord injury is associated with thalamic anatomical changes, the extent of which is correlated with pain intensity (Apkarian et al, 2004;Gustin et al, 2010). Furthermore, VP thalamic stimulation can produce pain (Lenz et al, 1993;Davis et al, 1996) and increased thalamic bursting activity and biochemical changes indicative of neuronal loss occur in patients with pain after spinal cord injury (Lenz et al, 1989;Pattany et al, 2002). In direct contrast to neuropathic pain conditions, pain associated with temporomandibular disorders (TMD) results primarily from the activation of peripheral nociceptors (Sarlani and Greenspan, 2005;Ro, 2008;Sessle et al, 2008;Manfredini and Nardini, 2010) and, furthermore, is associated with thalamic gray matter volume increases (Younger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%